Position of eukaryotic initiation factor eIF1 on the 40S ribosomal subunit determined by directed hydroxyl radical probing - Lomakin, Ivan B. (Cold Spring Harbor Laboratory Press, 2003)
Eukaryotic initiation factor (eIF) eIF1 maintains the fidelity of initiation codon selection by enabling 43S complexes to reject codon–anticodon mismatches, to recognize the initiation codon context, and to discriminate against establishing a codon–anticodon interaction with AUGs located <8 nt from the 5′-end of mRNA. To understand how eIF1 plays its discriminatory role, we determined its position on the 40S ribosomal subunit using directed hydroxyl radical cleavage. The cleavage of 18S rRNA in helices 23b, 24a, and 44 by hydroxyl radicals generated from Fe(II) tethered to seven positions on the surface of eIF1 places eIF1 on the interface surface of the platform of the 40S subunit in the proximity of the ribosomal P-site. The position of eIF1 on the 40S subunit suggests that although eIF1 is unable to inspect the region of initiation codon directly, its position close to the P-site is very favorable for an indirect mechanism of eIF1's action by influencing the conformation of the platform of the 40S subunit and the positions of mRNA and initiator tRNA in initiation complexes. Unexpectedly, the position of eIF1 on the 40S subunit was strikingly similar to the position on the 30S ribosomal subunit of the sequence and structurally unrelated C-terminal domain of prokaryotic initiation factor IF3, which also participates in initiation codon selection in prokaryotes.